2005
DOI: 10.1196/annals.1327.096
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution and Subfunctionalization of Nkx2.1 in the Rainbow Trout

Abstract: Because specification of duplicated genes is considered to be a major driving force for diversity and evolution, it is important to understand the function of the duplicated genes. In mammals, Nkx2.1 is essential for the differentiation of thyroid follicular cells and for the transcription of thyroid-specific genes. We have cloned four distinct Nkx2.1 cDNAs from the rainbow trout, Oncorhynchus mykiss. In the present article, we will characterize the trout Nkx2.1 mRNAs and show their tissue distribution, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…In addition, Pax9 is expressed in mammalian thyroid cell lines, although it does not mediate transcription from a 2-kb calcitonin (CT) promoter (Suzuki et al 2007) (see Table 1 for a list of endocrine organs and their secretions). In teleost fish, Pax1 and Pax9 are also expressed in the untimobranchial gland, a pharyngeal derivative (Suzuki et al 2005(Suzuki et al , 2007. Pax2 is also expressed in pancreatic islets, where it transcriptionally activates glucagon (Ritz-Laser et al 2000).…”
Section: The Evolution Of Chordate Pax Genesmentioning
confidence: 99%
“…In addition, Pax9 is expressed in mammalian thyroid cell lines, although it does not mediate transcription from a 2-kb calcitonin (CT) promoter (Suzuki et al 2007) (see Table 1 for a list of endocrine organs and their secretions). In teleost fish, Pax1 and Pax9 are also expressed in the untimobranchial gland, a pharyngeal derivative (Suzuki et al 2005(Suzuki et al , 2007. Pax2 is also expressed in pancreatic islets, where it transcriptionally activates glucagon (Ritz-Laser et al 2000).…”
Section: The Evolution Of Chordate Pax Genesmentioning
confidence: 99%
“…In zebrafish larvae, BPAF exposure decreases T3 and T4 levels and affects the expression of hypothalamus‐pituitary axis‐related genes, thereby causing thyroid endocrine disorders 41 . In this study, the expression levels of TH receptors ( trhr2 , trhra , trhrb , and thra ) and a gene related to the differentiation of thyroid follicular cells ( nkx2.1 ) have been evaluated 37,42–46 . Exposure to high concentrations of BPAF (5 mg/L) significantly damaged the thyroid function of embryos.…”
Section: Discussionmentioning
confidence: 99%
“…41 In this study, the expression levels of TH receptors (trhr2, trhra, trhrb, and thra) and a gene related to the differentiation of thyroid follicular cells (nkx2.1) have been evaluated. 37,[42][43][44][45][46] Exposure to high concentrations of BPAF (5 mg/L) significantly damaged the thyroid function of embryos.…”
Section: Bpaf Exposure Affects Thyroid Function In Marine Medaka Embryosmentioning
confidence: 99%
“…Yet, infusion of Mc4r antagonists mitigates the decreased feeding caused by TTF-1 antisense oligonucleotide (Kim et al, 2011). Mc4r acts as a functional receptor for POMC (Zhang et al, 2012) stimulated promoter transcription, comparable to Nkx2.1b, while Nkx2.1c only induced weak transcription and had different functions (Suzuki et al, 2005). In mandarin fish, Nkx2.1 contains three transcripts, and the most conserved transcript was selected to construct an overexpression vector.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the results of this experiment and those of mammals might be attributed to the fact that NKX2.1 has multiple copies in various species, and there are certain differences in functions between copies. In fish, Nkx2.1 in rainbow trout has four copies due to genome‐wide replication, among which Nkx2.1a and Nkx2.1c were found to be unique differentiation types of teleost fish, and each copy had different effects on the transcriptional activity of the promoter, and the luciferase intensity showed that Nkx2.1a significantly stimulated promoter transcription, comparable to Nkx2.1b, while Nkx2.1c only induced weak transcription and had different functions (Suzuki et al, 2005). In mandarin fish, Nkx2.1 contains three transcripts, and the most conserved transcript was selected to construct an overexpression vector.…”
Section: Discussionmentioning
confidence: 99%